The coexistence of write once read many memory and resistive memory in a single device of conjugated polymer - Nguyen, Viet Cuong (2017)
The thesis demonstrates for the first time coexistence of write once read many memory (WORM) with resistive random access memory (RRAM). This is the first time such coexistence phenomena are reported in organic materials system. Furthermore, better understanding of working mechanism in resistive switching phenomena in organic materials particularly conjugated polymer has been achieved. Two materials systems are chosen, namely, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT PSS) and Polyvinyl alcohol (PVA) where PEDOT PSS is a conducting polymer and PVA is an insulator polymer. For a device with 5 μm thick PEDOT PSS sandwiched between two Au electrodes, the coexistence of WORM memory and RRAM memory can be achieved (Chapter 4). The WORM result was attributed to dedoping of the conducting PEDOT + PSS- segments to insulating PEDOT 0 segments. The RRAM was explained due to Proton H+ conductive properties of PSS acid domains inside the film after dedoping. This points to a general feature: resistive switching behavior of a whole device is the result of additive/summative resistive switching characteristic of its components. Based on this, we reveal the coexistence of RRAM memory and WORM memory demonstrated in PEDOT PSS blend with PVA (Chapter 5). The WORM memory is again attributed to PEDOT PSS while RRAM memory is attributed to the charge trapping characteristic of PVA. The device performance is improved significantly as compared to the earlier PEFOT PSS system, with more than 1000 cycling stability and much more than 10^4 s retention for RRAM mode. Additional I-V characteristic of this device is further studied in chapter 6 which reveals a new type of WORM memory. This type of WORM memory is driven by metallic migration of Au electrodes.